Synthesis and Characterization of 2-(2-hydroxy-phenyl)-3-(-R- benzothiazol-2-yl) (Baghdad Science Journal, 2005)
were prepared by condensation of 6-R-2amino bcnzothiazol with Salicyldehyde.These Schiff bases were found to reach with maleic anhydride and citraconic to give